Red Light Exposure Delays Appearance and Aroma Deterioration of Fresh-Cut Watermelon during Retail Display - Yue Shi; Yubin Wang; Yue Ma; Yong Xu; Xiaoyan Zhao; Chao Zhang (Journal of Food Quality)
Appearance and aroma deterioration are the main concerns during the retail display of fresh-cut watermelons. Here, fresh-cut watermelons were exposed to the red, green, blue, and conventional white light at 4°C for 4 days, respectively, and their resulting qualities were compared with the conventional white light as the control. Specifically, the red light presented its maximum emissions in 620–650 nm with a purity of 100% and an intensity of 1104.7 lux. The red light exposure reduced the weight loss to 1.81%, which was reduced by 51.1% of the control. The red light exposure reduced the color difference of the fruit surface significantly as well as maintaining its redness. The water-soaking ratio of the red light exposure was also reduced by 62.8% of the control. Moreover, the red light exposure delayed the aroma deterioration, which resulted from both microbial metabolism and the self-metabolism of volatiles of the fresh-cut watermelon. In summary, the red light exposure was better to delay the appearance and aroma deterioration of fresh-cut watermelons than the conventional white light during their retail display.